Black women's perceptions of barriers to career advancement in the South African media industry. - Dlamini, Makhosazana Baby (My University, 2016)
Gender inequality remains a recurrent narrative in media institutions across the globe. Although employment figures indicate a surge in the number of women in the last decade, men continue to dominate the workplace, especially within senior management. Black women in South Africa face the dual challenge of race and gender thus limiting the career advancement within the industry. This study examines the perceptions of a sample of 20 black women in the media industry regarding the barriers to career advancement. The study seeks to identify the variety of barriers impeding the career advancement of women from the limiting workplace environment, stereotypes, attitudes of colleagues, the multiplicity of roles women play in the work place and in society. Finally, the study also highlights potential interventions for leveraging black women in advancing their careers and improving their status in the workplace. The research study was conducted based on a combination of the descriptive and causal research designs. Qualitative research methods were chosen for this study given that it was focused in unearthing and documenting subjective experiences of black female managers in the media industry. According to the findings of the study female black managers interviewed had ample opportunities to advance their careers within their organisations. All the women interviewed were in senior and executive management through both Affirmative Action (AA) and competence-based promotion. All the managers had at least a graduate qualification indicating that they possessed suitable qualifications for their positions. The study found that the advancement of black female managers is still hampered by stereotypes that denote women as secondary to men in the workplace. The research study found that the top five and major barriers to iii the career advancement of black women in the media industry are: balancing career and family responsibilities; office politics; skills and qualifications questioned; racial discrimination; and gender stereotypes. The study recommends that media institutions should formulate workplace policies and procedures that give women an equal chance of being recognised and make progress in their careers. Media Institutions should also make provision for female black managers to be exposed to career advancement opportunities through mentoring and training without discrimination. Female black managers also need to remain more vigilant in dismantling the gender and race biases in the workplace by taking proactive steps in demanding opportunities and advancing their careers.
MBA
Keywords: Sex discrimination in employment -- South Africa. Women, Black -- Employment -- South Africa.Executives, Black -- South Africa.Women in the mass media industry -- South Africa.